HUBUNGAN MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD NEGERI 166325 KOTA TEBING TINGGI T.A 2023/2024 - Sitanggang, Junjungan Natanael; Siregar, Arifin; Simanjuntak, Eva Betty; Mustika Aulia, Sri; Gandamana, Apiek (Jurnal Merah Putih Sekolah Dasar, 2024)
The problem of this research lies in the role of teachers in implementing classroom management as an effort to increase student learning motivation. The aim of this research is to determine the implementation of classroom management, the level of student learning motivation and correlation of classroom management towards learning motivation of class V students at SDN 166325 Tebing Tinggi City Academic Year 2023/2024. This research is a quantitative descriptive method correlation research. Sampling technique using saturated samples (total sampling) to obtain as many as 30 students as a sample of research, with 13 male students and 17 female students. Data collection techniques use observation, interviews, questionnaires and document study. The results of this research stated that the classroom management carried out was in the medium category (66,7%), students learning motivation was in the medium category (70,0%) and there was a significant correlations of classroom management towards learning motivation (Sig. value (p) of 0,000, where (p) < 0,05 and the Pearson Correlation (r) value is 0,632). The correlations between the two variables is in the strong correlation category and is positive correlation.Keywords: Classroom Management, Learning Motivation, Elementary School Students.